CCD Photometry of Comet 73P/Schwassmann-Wachmann 3 during Its 2006 Apparition Observed from the Bosscha Observatory - Budi Dermawan; P. Mahasena; Taufiq Hidayat; D. Mandey; Muhamad Irfan (Indonesian Journal of Physics, 2011)
On 9-10 May 2006 UT comet 73P/Schwassmann-Wachmann 3 (73P/SW3) passed 0.093 AU from the Earth, being slightly farther away than its discovery on 1930. Interestingly, it has been reported since 1995 that the comet has been breaking up to many components during its trajectory orbiting the Sun with a period of 5.4 years. Here we report our CCD photometric observations of major components B and C during its 2006 apparition. Successful observations were done on 12-14 May 2006 UT at the Bosscha Observatory, Lembang. Since comet is a moving object, we carried out stacking techniques to combine our images in order to strengthen the signal-to-noise ratio. Our investigations to their surface brightness show that the coma of 73P/SW3 was not in a steady state. Under assumption of a steady state coma, the dust production rate of the component is found to be 24.7 cm and the mass-loss rate of 4.94 kg s-1